E-therapists’ views on the acceptability and feasibility of an internet-administered, guided, low-intensity cognitive behavioural therapy intervention for parents of children treated for cancer: A qualitative study ... - Reuther, Christina; Lundgren, Johan; Gottvall, Maria; Ljungberg, Johan; Woodford, Joanne; Essen, Louise von (SAGE Journals, 2024)
BackgroundChildhood cancer treatment completion can be a period of vulnerability for parents and is associated with mental health difficulties such as depression and anxiety. We developed an internet-administered, guided, low-intensity cognitive behavioural therapy-based self-help intervention (EJDeR) for parents delivered on the U-CARE-portal (Portal). The acceptability and feasibility of EJDeR and study procedures were examined using a single-arm feasibility trial (ENGAGE). Results indicated that EJDeR and ENGAGE study procedures are acceptable and feasible, however, a need for clinical and technical modifications to EJDeR and refinements to ENGAGE study procedures was identified.ObjectivesThis study aimed to explore the acceptability and feasibility of EJDeR and ENGAGE study procedures from the perspective of e-therapists to inform clinical and technical modifications to EJDeR and refinements to study procedures prior to progression to a superiority randomised controlled trial.MethodsWe conducted ...